Bimodal Programming: A Survey of Current Clinical Practice. - Siburt, Hannah W.; Holmes, Alice E. (American Journal of Audiology, 2015)
Purpose: The purpose of this study was to determine the current clinical practice in approaches to bimodal programming in the United States. To be specific, if clinicians are recommending bimodal stimulation, who programs the hearing aid in the bimodal condition, and what method is used for programming the hearing aid? Method: An 11 -question online survey was created and sent via email to a comprehensive list of cochlear implant programming centers in the United States. The survey was sent to 360 recipients. Results: Respondents in this study represented a diverse group of clinical settings (response rate: 26%). Results indicate little agreement about who programs the hearing aids, when they are programmed, and how they are programmed in the bimodal condition. Analysis of small versus large implant centers indicated small centers are less likely to add a device to the contralateral ear. Conclusions: Although a growing number of cochlear implant recipients choose to wear a hearing aid on the contralateral ear, there is inconsistency in the current clinical approach to bimodal programming. These survey results provide evidence of large variability in the current bimodal programming practices and indicate a need for more structured clinical recommendations and programming approaches.